2007
DOI: 10.4141/a06-051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allometric space allowance and weight group composition on grower-finisher pigs

Abstract: Anil, L., Anil, S. S. and Deen, J. 2007. Effects of allometric space allowance and weight group composition on grower-finisher pigs. Can. J. Anim. Sci. 87: 139-151. The average daily gain (ADG; kg d -1 ), pen efficiency (PE; kg ADG m -2 floor space) and welfare indicators (injury levels, salivary cortisol concentrations and behaviour) of grower-finisher pigs were evaluated in groups of 19 barrows, at four levels of floor space allowances calculated mathematically (area = k × BW 0.667 ) using a constant k, (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 49 publications
6
41
1
1
Order By: Relevance
“…results in increased incidence of abnormal behavior, including nosing, aggressions and tail biting (Anil et al, 2007).…”
mentioning
confidence: 99%
“…results in increased incidence of abnormal behavior, including nosing, aggressions and tail biting (Anil et al, 2007).…”
mentioning
confidence: 99%
“…Resting behaviour appears to be strongly related to space allowance, with different studies covering this issue during recent years (Anil et al, 2007a;Scott et al, 2007a;Street and Gonyou, 2008;Hötzel et al, 2009;Li and Johnston, 2009). Allometric principles show increasing evidence of their suitability when calculating the spatial needs of pigs according to their behaviour ).…”
Section: Ability To Rest and Sleep (C73)mentioning
confidence: 99%
“…) Recent studies suggest that increasing space allowance may be a successful means of reducing the prevalence of aggressive behaviours among finishing pigs. Anil et al (2007a) showed that, for k values ranging between 0.027 and 0.037 at BW = 116 kg, increasing space allowance reduced the number of aggressive interactions and the total injury scores in growing-finishing pigs housed on slatted floors. Similarly, Liorancas et al (2006) comparing different space allowances in growingfinishing pigs found that the pigs were more inactive and spent more time fighting and biting when housed in pens with a k value of 0.021, at the moment of slaughter, compared to k=0.050.…”
Section: 42mentioning
confidence: 99%
See 1 more Smart Citation
“…Overcrowding may suppress pigs’ biological functioning (e.g., normal growth) and expression of natural behaviours [9, 10]. Obstruction in expression of pigs’ natural behaviours (e.g., exploration or chewing of objects) may trigger tail-biting, ear-chewing, aggression, and fighting [11, 12]. In addition to overcrowding, restricting vehicles into movement restriction areas may interrupt feed supply for swine premises, which can have an immediate impact on the well-being of pigs [13, 14].…”
Section: Introductionmentioning
confidence: 99%